Board Gender Diversity and Investment Efficiency: Global Evidence from 83 Country-Level Interventions - Baik, Dave; Chen, Clara Xiaoling; Godsell, David (The Accounting Review, 2024)
ABSTRACT We investigate the effect of board gender diversity (BGD) on investment outcomes. We identify variation in BGD by compiling, for the first time, a global catalog of 83 BGD interventions implemented in 59 countries between 1999 and 2021. Using a staggered difference-in-differences research design, we document that BGD interventions improve investment outcomes. We find that treated firms reduce inefficient investment by 0.6 percent of total assets or 6.5 percent of total investment and are 4 percentage points more likely to have above-median investment efficiency. Cross-sectional tests reveal more pronounced results when BGD interventions are mandatory, are strongly enforced, and result in larger BGD increases. Event-time, stacked panel, and a wide variety of endogeneity-mitigating robustness tests corroborate. Our plausibly causal inferences have important implications for both research and practice. JEL Classifications: F52; G34; G38; K22; M41; K38.